Low-temperature solution-processed zinc oxide field effect transistor by blending zinc hydroxide and zinc oxide nanoparticle in aqueous solutions. (3rd April 2018) - Shin, Hyeonwoo; Kang, Chan-mo; Baek, Kyu-Ha; Kim, Jun Young; Do, Lee-Mi; Lee, Changhee
Abstract: We present a novel methods of fabricating low-temperature (180 °C), solution-processed zinc oxide (ZnO) transistors using a ZnO precursor that is blended with zinc hydroxide [Zn(OH)2 ] and zinc oxide hydrate (ZnO ∙ H2 O) in an ammonium solution. By using the proposed method, we successfully improved the electrical performance of the transistor in terms of the mobility (μ), on/off current ratio ( I on / I off ), sub-threshold swing ( SS ), and operational stability. Our new approach to forming a ZnO film was systematically compared with previously proposed methods. An atomic forced microscopic (AFM) image and an X-ray photoelectron spectroscopy (XPS) analysis showed that our method increases the ZnO crystallite size with less OH − impurities. Thus, we attribute the improved electrical performance to the better ZnO film formation using the blending methods.